DIGITAL PEDAGOGICAL COMPETENCIES OF PHYSICAL EDUCATION TEACHERS - Kovalevskaya, Ekaterina; Kolbasova, Irina; Mititsina, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The global COVID-19 pandemic has changed the education system. The use of modern information technologies in the educational process and the introduction of distance learning are becoming more and more relevant. These requirements began to apply to academic disciplines, which a priori are difficult to teach online, in a quarantine situation. Physical education is such a discipline. Requirements for teachers are increasing. The teacher must have digital pedagogical competencies in order to successfully teach this academic discipline in modern conditions. The purpose of this pilot study was to determine the level of formation of digital pedagogical competencies among physical education teachers working in institutions of higher and secondary vocational education. The research is based on the European model Digital Competence of Educators (DIGCOMPEDU). A questionnaire for identifying the formation of digital pedagogical competencies was developed on the basis of this model and tested in this study. Teachers were asked to assess, on a 5-point scale, the level of skills and experience in the application of information technologies in the educational process and in the organization of distance learning, as well as to provide specific resources with which they work.44 teachers of physical education from Pskov State University, College of Pskov State University and Velikie Luki State Academy of Physical Culture and Sports took part in this study. It was found that most of all physical culture teachers have formed the ability to work with search engines and knowledge in the field of information security. The skills to produce and use video and graphics content are the least developed. Also an important problem is the lack of experience in the implementation of distance learning among physical education teachers.Groups of teachers with different levels of formation of digital pedagogical competencies were identified using cluster analysis. Five such levels have been identified.The conducted research determines the problem that physical education teachers lack competence in the field of information technologies and their implementation in the educational process even with a mixed form of education (full-time form with elements of distance learning).